Unleashing the anti-tumor angiogenic potential of nano-formulated orientin: In Silico, In Vitro, and In Ovo studies - Yashwanth Elumalai; Kathiresan Nachammai; Kirubhanand Chandrasekaran; Langeswaran Kulanthaivel; Sharon Benita Stephen; Kanu Shil; Ram Kumar Anandan; Abdulhadi Ibrahim Bima; Zeenath Khan; Abdulhadi S. Burzangi; Noor A. Shaik; Nuha Al-Rayes; et al. (PLoS ONE, 2025)
The study investigated the potential of nano-formulated orientin (NF-O) in the anti-angiogenic cancer therapy. Orientin is a flavonoid that has a promising effect against anti-inflammatory, anti-oxidant, and anti-arrhythmia properties. Nano-formulation aimed to overcome this limitation and also served to enhance its therapeutic efficacy. In silico docking studies, the favorable binding of orientin was identified with the key oncogenic targets (EGFR, ALK, KRAS, NTRK). After nano-formulation, UV spectroscopy confirmed the integrity of orientin with no shift in the λmax (347 nm). Dynamic light scattering showed a significant reduction in the improved particle size (PDI decreased from 0.863 to 0.173) by nano-formulation from 559 nm to 220 nm. Fourier Transform infrared spectroscopy analysis confirmed that the nano-formulation process did not alter the chemical structure of orientin. In-vitro studies using MCF-7 breast cancer cells showed that NF-O inhibited cell growth and reduced viability in a dose-dependent manner. At 10 µM, NF-O significantly inhibited the cell growth and migration compared to the control and native orientin in wound healing assays (p < 0.01). In ova, using the chick chorioallantoic membrane (CAM) assay, NF-O (10 µg/ml) significantly inhibited angiogenesis by reducing blood vessel density, branching, length, and network formation compared to controls and native orientin. These findings suggest that NF-O holds significant promise as a novel anti-angiogenic agent for the cancer treatment.